2009
DOI: 10.1177/1756283x08101217
|View full text |Cite
|
Sign up to set email alerts
|

Review: Rapid virological response to peginterferon alfa and ribavirin treatment of chronic hepatitis C predicts sustained virological response and relapse in genotype 1 patients

Abstract: The treatment of chronic hepatitis C is a rapidly changing arena with new medications, new guidelines, and an evolving understanding of the virus, host factors and natural history. With the explosion of new information, the educational infrastructure to update clinicians has been outpaced; many feel uncertain if the tools they are using to care for patients are meeting the standard of practice. This review focuses on the most common genotype of the hepatitis C virus and the rules of engagement when treating wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In the present study, when patients were divided in the same way as in Hamdi et al's study (15), their results were confirmed (data not shown). Additionally, the p53 expression level was compared between RVRs (strong positive predictor for SVR) (9,37) and non-RVRs, as well as between NRs (strong negative predictor for SVR) (5) and non-NRs to confirm the lack of usefulness of p53 expression in predicting the response to anti-HCV therapy (data not shown). The association between p53 expression and the response to anti-HCV treatment was analyzed by Loguercio et al (22) at the protein level in liver samples.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, when patients were divided in the same way as in Hamdi et al's study (15), their results were confirmed (data not shown). Additionally, the p53 expression level was compared between RVRs (strong positive predictor for SVR) (9,37) and non-RVRs, as well as between NRs (strong negative predictor for SVR) (5) and non-NRs to confirm the lack of usefulness of p53 expression in predicting the response to anti-HCV therapy (data not shown). The association between p53 expression and the response to anti-HCV treatment was analyzed by Loguercio et al (22) at the protein level in liver samples.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the presence of RVR is highly predictive of ultimate SVR with a full treatment course of 48 wk in genotype 1 patients [22] . In the current study, all genotype 1 patients (n = 7) who achieved RVR also attained SVR; while a study reported a SVR rate of 86.8% in patients with RVR [15] .…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to IL28B genotype, absolute lymphocyte counts and the fall in viral load are both continuous variables determined by the patient history and response -particularly at week 1 when these data were particularly influential in our model. Several previous reports suggest that rapid virological response or viral response within two weeks of starting treatment are stronger predictors of SVR [29,30] than even a ≥ 2-log 10 decrease in HCV RNA, low-level detectable HCV RNA at week 4 or an undetectable level by week 12 of therapy [19,31,32]. The current study indicates that a viral load fall of either 80% at week 1, or 90% at week 2 appears to be a better predictor of response than viral load itself.…”
Section: Discussionmentioning
confidence: 99%